Root nodules in Chilean conifers - Grez Z., Renato (Bosque (Valdivia), 1988)
Root nodulation in Chilean conifers is described, particularly in Araucariaceae and Podocarpaceae. The nodules are spherical and brownish yellow in Podocarpaceae -varying in diameter among species- while in Araucariaceae they are like elongated reddish spheres.